2004
DOI: 10.1257/0022051043004595
|View full text |Cite
|
Sign up to set email alerts
|

Job Information Networks, Neighborhood Effects, and Inequality

Abstract: JOB INFORMATION NETWORKS, NEIGHBORHOOD EFFECTS AND INEQUALITY Yannis M. Ioannides and Linda Datcher LouryThe paper explores the theoretical and empirical literature to examine the use by different social groups of informal sources of information provided by friends, relatives and acquaintances during job search and its consequences for the job market. It also addresses the role of network structure and size, the resource endowments of contacts, and nature of the links between contacts to explain differences in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
537
1
21

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 933 publications
(591 citation statements)
references
References 85 publications
32
537
1
21
Order By: Relevance
“…A number of studies have found that social networks can lead to economic opportunities, efficient transactions and ultimately to economic growth as they allow people to 'leverage on resources' such as knowledge and information of members in the network (Lin, 1999;Mouw 2003;Ioannides and Loury, 2004). The positive role of social capital on individuals' labour market outcomes has been the subject of considerable research, with a growing interest by economists to study the impact of social networks on labour market outcomes in terms of employment entry and wages.…”
Section: Social Capital and The Labour Marketmentioning
confidence: 99%
“…A number of studies have found that social networks can lead to economic opportunities, efficient transactions and ultimately to economic growth as they allow people to 'leverage on resources' such as knowledge and information of members in the network (Lin, 1999;Mouw 2003;Ioannides and Loury, 2004). The positive role of social capital on individuals' labour market outcomes has been the subject of considerable research, with a growing interest by economists to study the impact of social networks on labour market outcomes in terms of employment entry and wages.…”
Section: Social Capital and The Labour Marketmentioning
confidence: 99%
“…The name ''Rotary" derived from the early practice of rotating meetings among members' offices." 8 See also Granovetter (1995) on how social capital improves welfare through the creation of an efficient network comprising social ties that allows for better expectations; Ioannides and Loury (2004) on how networks affect labor-market outcomes and inequality; Montgomery (1991) on the importance of referrals to outcomes on the labor market. 9 The dataset used by Belot and Ermisch (2006) allows them to explore other instruments to describe the environment in which the individual spent his/her childhood.…”
Section: Setupmentioning
confidence: 99%
“…Survey evidence gathered across countries and over time has consistently indicated that between one third and one half of job matches are created through friends and relatives (see e.g. Loury, 2004, andTopa, 2011). Despite the importance of the use of contacts in job search, there is limited empirical evidence on the effect of network quality on labor market outcomes.…”
Section: Introductionmentioning
confidence: 99%